PENGARUH PROFITABILITAS, LEVERAGE, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2015-2019 - Christili Tanjaya; Nazmel Nazir (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This research’s purpose is to examine the influence of profitability, leverage, sales growth, and firm size on tax avoidance in consumer goods manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. The proxy of tax avoidance is Effective Tax Rate/ETR. The secondary data used as data source is the financial reports of sample companies. Purposive sampling is used as the sampling method. The samples that met the criteria are 105 samples. The data analysis is multiple linear regression and is processed using EViews 9 program. The results showed that profitability has a significant positive effect on tax avoidance; leverage and sales growth have no significant effect on tax avoidance; and firm size has a significant negative effect on tax avoidance.